Low Latitude Analysis of Geomagnetic Storm Effects on Ionospheric Vertical Drifts over the East African Region - Niwamanya, Duncan; Habyarimana , Valence; Jurua, Edward (Atmospheric and Climate Sciences, 2025)
The geomagnetic storm effect on ionospheric vertical E × B drift is analysed using Communication/Navigation Outage and Forecasting System (C/NOFS) Satellite data, magnetometer data, and solar wind data, over the East African low latitude region during the period 2008-2015. We identified a total of 608 corotating interaction region (CIR)-driven and 23 coronal mass ejection (CME)-driven geomagnetic storms in this study. Most of the CIR-driven storms were observed during the declining phase of solar cycle 24 in 2015. The CME-driven storms, on the other hand, were dominant during the near maximum phase of the solar cycle 24 in 2012. The C/NOFS satellite data was found to be consistent with magnetometer observations in identifying both upward and downward vertical E × B drift occurrence. The common result of analysed CME-driven geomagnetic storms was enhancement in E × B drifts due to presence of eastward prompt penetrating electric fields (PPEFs) during the storm main phase. There was also a decrease in E × B due to the decrease in horizontal component of the magnetic field ( ΔH ) during the recovery phases of the CME-driven storms. This is a manifestation of downward E × B drifts associated with westward electric field, which is due to the disturbance dynamo contribution. During CIR-driven geomagnetic storms, the storm’s main phases were also dominated by downward E × B drifts associated with westward electric field, which is due to disturbance dynamo.